2013
DOI: 10.1596/1813-9450-6670
|View full text |Cite
|
Sign up to set email alerts
|

What Have We Learned from the Enterprise Surveys regarding Access to Credit by SMEs?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 13 publications
6
100
0
8
Order By: Relevance
“…Meisenzahl (2011), Angelini, andGenerale (2008) and Kuntchev et al (2012) are among the studies that take this approach. Even though the response by the firm is not directly verifiable by the research, one should expect it to be, on average, a good, firsthand proxy for financial constraints.…”
Section: Second a Firm Is Financially Constrained If It Describes mentioning
confidence: 99%
“…Meisenzahl (2011), Angelini, andGenerale (2008) and Kuntchev et al (2012) are among the studies that take this approach. Even though the response by the firm is not directly verifiable by the research, one should expect it to be, on average, a good, firsthand proxy for financial constraints.…”
Section: Second a Firm Is Financially Constrained If It Describes mentioning
confidence: 99%
“…and Cole and Dietrich (2014) used the WBES database to show that there was a robust correlation around the world (including the LAC region) between firm size and access to finance and that SMEs were more likely to face credit constraints. Kuntchev et al (2013) also found that internationalized and more productive firms were less likely to suffer from difficulties in accessing credit, with the latter association being stronger for larger firms. Specifically using WBES data for Argentina, Brazil, Chile, and Mexico, Makler et al (2013) supported the standard hypothesis that smaller and younger firms are disadvantaged when it comes to securing bank credit compared to larger and older enterprises.…”
Section: Firm-level Characteristicsmentioning
confidence: 83%
“…This result is consistent with most other studies attempting to quantify the impact of firms' access to line of credit from a financial institution. Kuntchev et al (2013) finds a significant positive impact of access to credit and firms' productivity in developing countries in general. Asiedu et al (2013) reached similar conclusion for firms in Sub-Saharan Africa.…”
Section: Performance Outcome Differences: Regressions and Matching Inmentioning
confidence: 96%